Numerical solution of a thermomechanical boundary-value problem for crystallizing viscoelastic polymer - Kulikova, Tatyana Georgievna; Trufanov, Nikolay Alexandrovich (Computational Continuum Mechanics, 2008)
A formulation of the thermomechanical boundary-value problem for crystallizing polymeric media considering the viscoelastic properties of the polymer is presented. The algorithms for numerical realization of thermo-kinetic and mechanical problems of a solidifying system in axisymmetric case are considered. The peculiarities of the numerical solution of the mechanical problem are discussed. The solution to the problem of technological stress formation at a permanent joint of steel and polyethylene pipes is given